PENGARUH JARAK LASER HEAD TERHADAP DIAMETER SPOT PADA PEMOTONGAN POLYMETHYL METHACRYLATE MENGGUNAKAN MESIN LASER CUTTING (P3M Politeknik Negeri Cilacap, 2018)
Laser cutting is one of the processes used as an alternative to conventional machinery that has goodcutting qualities and minimizes product damage. The workings of laser cutting is to direct the output of high laser power on the material to be cut, the material then melts, burns, evaporates by gas, and produces edges with a good quality surface. This study aims to determine the effect of laser head distance from the laser cutting machine on the spot diameter produced on the polymethyl methacrylate (PMMA) material. This study used a laser machine with 60 watts of power and variation of laser head distance with an interval of 1 mm at a distance of 1-28 mm. Spot diameter value was gained measurement from using stereo zoom microscope with 30 X magnification and mapping. The result shows that the spot diameter was 0,229 - 0,990 mm. The factors that affect the value of spot diameter is the laser power used and laser head distance from the material.